Penerapan Metode Scramble Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas I SD Negeri Bugel - Venny Febriani; Siti Rochmiyati (Jurnal Pendidikan Indonesia (JOUPI), 2023)
In erveryday life, we can’t be separated from the use of language as a means of communication. Language is used as the main communication tool for humans to express ideas, feelings, and desires. One of focus of the language learning in elementary schools that plays an important role is learning to read. Children will experience learning difficulties in the future if they don’t have adequate reading skills from an early age. This reading ability is the main basis not only for learning the language itself, but also for learning ither subjects. Children’s interest in reading activities can be habituated by carrying out literacy activities regularly and continously. The aim of this research is to analyze the implementation of scramble method to improve initial reading skills for class I student at SD Negeri Bugel. This research use a qualitative research design. The result of this research show that through implementing scramble method, class I students become more enthusiastic in learning so that their initial reading ability increases.